Is Exercise Protective Against Influenza-Associated Mortality? - Wong, Chit-Ming; Lai, Hak-Kan; Ou, Chun-Quan; Ho, Sai-Yin; Chan, King-Pan; Thach, Thuan-Quoc; Yang, Lin; Chau, Yuen-Kwan; Lam, Tai-Hing; Hedley, Anthony Johnson; Peiris, Joseph Sriyal Malik (PLOS ONE, 2008)
BackgroundLittle is known about the effect of physical exercise on influenza-associated mortality.Methods and FindingsWe collected information about exercise habits and other lifestyles, and socioeconomic and demographic status, the underlying cause of death of 24,656 adults (21% aged 30–64, 79% aged 65 or above) who died in 1998 in Hong Kong, and the weekly proportion of specimens positive for influenza A (H3N1 and H1N1) and B isolations during the same period. We assessed the excess risks (ER) of influenza-associated mortality due to all-natural causes, cardiovascular diseases, or respiratory disease among different levels of exercise: never/seldom (less than once per month), low/moderate (once per month to three times per week), and frequent (four times or more per week) by Poisson regression. We also assessed the differences in ER between exercise groups by case-only logistic regression. For all the mortality outcomes under study in relation to each 10% increase in weekly proportion of specimens positive for influenza A+B, never/seldom exercise (as reference) was associated with 5.8% to 8.5% excess risks (ER) of mortality (P<0.0001), while low/moderate exercise was associated with ER which were 4.2% to 6.4% lower than those of the reference (P<0.001 for all-natural causes; P = 0.001 for cardiovascular; and P = 0.07 for respiratory mortality). Frequent exercise was not different from the reference (change in ER −0.8% to 1.7%, P = 0.30 to 0.73).ConclusionWhen compared with never or seldom exercise, exercising at low to moderate frequency is beneficial with lower influenza-associated mortality.